Symbolic Violence of Patriarchy: Forms of Physical and Verbal Bullying Against Alie in Lenn Liu's Novel Rumah Untuk Alie - Destilawati Noho; Sitti Rachmi Masie; Herman Didipu (Raja Zulkarnain Education Foundation, 2026)
This study aims to describe the forms of physical and verbal bullying experienced by the character Alie in the novel Rumah untuk Alie by Lenn Liu and analyze the representation of symbolic patriarchal violence in family relations. The study was conducted at the Gorontalo State University Library from January to March 2026. The research population was the entire text of the novel Rumah untuk Alie, fifth edition (2024, 262 pages), with samples in the form of words, phrases, sentences, and paragraphs that contain indications of physical and verbal bullying against the character Alie. The main data sources are presented in the form of story excerpts containing bullying. The research instrument was the researcher herself assisted by a bullying classification table based on Coloroso’s typology. The data analysis technique used feminist literary criticism with the steps of text identification, interpretation, and drawing conclusions. The results of the study show that Alie experienced various forms of physical bullying, such as hitting, kicking, hair pulling, grabbing, pushing, dragging, throwing, hitting, and physical harassment. In addition, Alie also experiences verbal bullying in the form of insults such as “murderer”, “whore” and “daughter of a servant”, threats “JUST DIE!”, accusations, shouts, and curses. Most of the bullying comes from her father (Abimanyu) and her four older brothers (Sadipta, Rendra, Samuel, Natta). This physical and verbal bullying represents symbolic patriarchal violence carried out through three simultaneous mechanisms: stigmatization, legitimization, and isolation. Thus, the novel critiques the weak protection of victims of domestic violence in Indonesia.